ANAK-ANAK SEBAGAI KORBAN KEJAHATAN SEKSUAL DARI ORANG DEWASA - Antoni, Antoni (Universitas Islam Negeri Raden Fatah Palembang, 2015)
Abstract: The child is a time of joy and excitement and this iswhere the future growth and small flowers . On the other handviolence done to children is common. A series of sexual abuse ofchildren is not just a physical mark on their little bodies, butalso to make an impression in the soul of a child until he grewup. One day later not blame them, when they tend to do thingsthat deviate. This article will discuss the position of the child asan object of sexual violence legal philosophy perspectiveملخص: الطفولة ھي فترة من الفرح والإثارة وھذا ھو المكان نمو و أزھار الطفولة فيالمستقبل. على العنف جھة أخرى القیام بھ للأطفال شائعة. وھناك سلسلة من الاعتداءالجنسي على الأطفال لیس فقط أن یكون بصمة جسدیا على أجسادھم الصغیرة، ولكنأیضا جعل انطباعا في النفس للطفل حتى نشأ وترعرع. في وقت لاحق یوم واحد لاألومھم، عندما تمیل إلى فعل الأشیاء التي تحید. ھذه المادة سوف یناقش وضع الطفلككائن العنف الجنسي منظور الفلسفة القانونیة.Kata Kunci: Kejahatan terhadap anak